2003
DOI: 10.1093/pcp/pcg149
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Plastidic Glucose Translocator is Expressed in Heterotrophic Tissues that do not Contain Starch, during Olive (Olea europea L.) Fruit Ripening

Abstract: ;Metabolite-specific transporters are present in the inner membrane of the plastid envelope allowing transport between the plastid and other cellular compartments. A plastidic glucose translocator (pGlcT) in leaf mesophyll cells transports glucose from chloroplast stroma to the cytosol after amylolytic starch degradation at night. Here we report the cloning of a pGlcT expressed in olive fruits (Olea europea L.). Our results showed high expression of pGlcT in non-green heterotrophic fruit tissues. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The presence of the tomato plastidic hexokinase LeHxk4 in starchless tissues suggests that LeHxk4 phosphorylates imported glucose in fruits rather than glucose originating from starch breakdown. Importing glucose into plastids of tomato red fruits is in agreement with our previous Wnding of a plastidic glucose transporter, LeGLT, expressed at diVerent developmental stages of tomato fruits including red fruits (Butowt et al 2003).…”
Section: Expression Analysis Of Lehxkssupporting
confidence: 91%
“…The presence of the tomato plastidic hexokinase LeHxk4 in starchless tissues suggests that LeHxk4 phosphorylates imported glucose in fruits rather than glucose originating from starch breakdown. Importing glucose into plastids of tomato red fruits is in agreement with our previous Wnding of a plastidic glucose transporter, LeGLT, expressed at diVerent developmental stages of tomato fruits including red fruits (Butowt et al 2003).…”
Section: Expression Analysis Of Lehxkssupporting
confidence: 91%
“…3). Most of the reported plasma membrane monosaccharide transporters and the three plastid-localized monosaccharide transporters OepGlT, SocTP1 and MccTP1 (Hausler et al 2000;Weber et al 2000;Butowt et al 2003) were selected for the phylogenetic analysis in order to demonstrate whether OsMST4 is phylogenetically more closely related to the plasma membrane-localized monosaccharide transporters or to the plastid-localized monosaccharide transporters. OsMST4 is highly homologous to plasma membrane H + -monosaccharide symporters from higher plants, showing highest homology to tomato LeHT2 (80.2% amino acid identity), a functional H + -glucose symporter (Gear et al 2000), and clearly separated from the three plastid-localized monosaccharide transporters OepGlT, SocTP1 and MccTP1, and from barley HvSTP1 and HvSTP2 (Weschke et al 2003).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Most of the identified plant monosaccharide transporters are proved or supposed to be located in the plasma membrane . Most recently monosaccharide transporters located in chloroplast have been cloned from spinach, Mesembryanthemus crystallinum and olive (Hausler et al 2000;Weber et al 2000;Butowt et al 2003), and the presence of monosaccharide transporters in plant mitochondria, Golgi and vacuole has also been reported (Chiou and Bush 1996;Szarka et al 2004;Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of FRK in plastids is quite surprising since, unlike glucose, the source of fructose within plastids is not clear. Fructose could be either transported into plastids by an as yet unknown fructose (or hexose) transporter such as the recently identiWed plastidic glucose translocator (Butowt et al 2003), or formed within plastids following cleavage of sucrose by either invertase or sucrose synthase. The presence of sucrose in plastids has been suggested (Gerrits et al 2001), but no plastidic invertase or sucrose synthase have been reported.…”
Section: Prediction and Analysis Of The Intracellular Locations Of Tomentioning
confidence: 99%